Examen especial a la cartera de microcréditos de la cooperativa de ahorro y crédito indígena “Sac Latacunga” ltda de la provincia de Cotopaxi por el ejercicio económico 2020 - Cachumba Simbaña, Magaly Geomara (2023)
The objective of the research project is to examine the microcredit portfolio of the "Cooperativa de Ahorro y Credito Indígena "SAC Latacunga" Ltda., of the province of Cotopaxi for the fiscal year 2020, through a special audit examination, it is carried out Fundamentally to know the management and operation of the accounts belonging to this item. The methodologies that are applied in the investigation are documentary-bibliographic and field; The first used the compilation of the scientific and theoretical support of this research, the second allowed the collection of first-hand information through interviews and questionnaires applied to the management of the cooperative, the accounting, credit and collection departments, as well as to the clients of the cooperative.